The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/1521-3862(200010)6:5<233::aid-cvde233>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Volatile CeIII Hexafluoroacetylacetonate Glyme Adducts as Promising Precursors for the MOCVD of CeO2 Thin Films

Abstract: Three novel monomeric glyme adducts of cerium hexafluoroacetylacetonate (Ce(hfa) 3 ×diglyme 1, Ce(hfa) 3 ×diethyldiglyme 2, and Ce(hfa) 3 ×dibutyldiglyme 3) have been synthesized adopting a one-pot procedure and characterized by elemental analyses, mass spectrometry, and infrared spectroscopy. Single-crystal X-ray diffraction (XRD) studies provide evidence of a mononuclear nine-coordinated complex with a monocapped square antiprismatic structure of the Ce(hfa) 3 ×diglyme (monoclinic system, space group = P2 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Pollard et al 368 designed new glyme-adduct precursors of [Ce(hfac) 3 (glyme)] (glyme = mono-, di-, or tri-) and [(Ce(hfac) 3 ) 2 (μ-tetraglyme)] and used them in the CVD formation of films of cerium oxides on substrates Si, Pt, and TiN. The Fragalà group 369 also prepared Ce(hfac) 3 ·diglyme, Ce(hfac) 3 ·diethyldiglyme and Ce(hfac) 3 ·dibutyldiglyme, and found these complexes are ideal for CeO 2 film depositions due to their high volatility and high thermal stability with low residue. Malandrino et al 370 synthesized novel complex precursors Eu(hfac) 3 ·glyme (glyme = mono- or di-) and found that both complexes are thermally stable and could be evaporated with < 4% residue.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Pollard et al 368 designed new glyme-adduct precursors of [Ce(hfac) 3 (glyme)] (glyme = mono-, di-, or tri-) and [(Ce(hfac) 3 ) 2 (μ-tetraglyme)] and used them in the CVD formation of films of cerium oxides on substrates Si, Pt, and TiN. The Fragalà group 369 also prepared Ce(hfac) 3 ·diglyme, Ce(hfac) 3 ·diethyldiglyme and Ce(hfac) 3 ·dibutyldiglyme, and found these complexes are ideal for CeO 2 film depositions due to their high volatility and high thermal stability with low residue. Malandrino et al 370 synthesized novel complex precursors Eu(hfac) 3 ·glyme (glyme = mono- or di-) and found that both complexes are thermally stable and could be evaporated with < 4% residue.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[20,21] We have recently reported on a novel class of complexes, known as "second-generation" precursors, the framework of which combines fluorinated b-diketonate arrays and ancillary coordinated polyethers, thus providing monomeric, volatile, and thermally stable rare-earth metal sources. [22][23][24][25][26][27] The Ln(hfa) 3 glyme adducts have been widely applied to various materials ranging from the complex perovskitebased oxides such as LaAlO 3 [28][29][30] and La 2-x Ba x CuO 4+d phases, so represent particularly suited single-source precursors for the MOCVD of LnF 3 or LnOF. In this paper, we report on the deposition of lanthanumcontaining films from the single-source MOCVD precursor La(hfa) 3 diglyme (Hhfa = 1,1,1,5,5,5-hexafluoroacetylacetone, diglyme = bis(2-methoxyethyl)ether).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ''M͑hfa͒ n '' ␤-diketonates consist of water-coordinated complexes which show a quite low vapor pressure because of H bondings and, even more important, decompose upon heating. Finally, ''M͑hfa) 3 glyme'' adducts already synthesized in the case of other rare earths elements such as La, Ce, Gd, and Eu have been tested [25][26][27][28][29] and proved to be good MOCVD precursors for the deposition of rare earth simple or mixed oxides ͑i.e., CeO 2 and LaAlO 3 ) thin films in a wide range of substrates. [40][41][42] In this context, the synthesis of the new Pr͑hfa͒ 3 •diglyme precursor must be placed.…”
Section: Discussionmentioning
confidence: 99%
“…Note, in this context, that using the Ce͑hfa͒ 3 •diglyme precursor, high quality CeO 2 films have been obtained. 26,40 Therefore, the problem of unwanted fluorinated phases should be addressed time by time, depending on the metallic nature and thermodynamic stability of the desired phase.…”
Section: Discussionmentioning
confidence: 99%